Functionalized polyhedral oligosilsesquioxane (POSS) based composites for bone tissue engineering: synthesis, computational and biological studies. Issue 19 (19th March 2020) - Legnani, Laura; Iannazzo, Daniela; Pistone, Alessandro; Celesti, Consuelo; Giofrè, Salvatore; Romeo, Roberto; Di Pietro, Angela; Visalli, Giuseppa; Fresta, Monica; Bottino, Paola; Blanco, Ignazio; Chiacchio, Maria Assunta
Abstract : Functionalized POSS containing an isoxazolidine nucleus have been synthesized by 1, 3-dipolar cycloaddition and conjugated with chitosan for bone tissue engineering applications. Abstract : Functionalized polyhedral oligosilsesquioxanes (POSS) containing an isoxazolidine nucleus have been synthesized by microwave assisted 1, 3-dipolar cycloaddition of N -methyl- C -alkoxycarbonyl nitrone 1 with POSS containing olefin moieties. The results of cycloaddition processes were rationalized by computational studies at the DFT level. The covalent conjugation of chitosan with the cycloadduct 3a leads to composite material CS-POSS 7 which was gelified using genipin as cross linking agent. The suitability of the system for bone tissue engineering purposes was evaluated by in vitro drug release studies using ketoprofen as a model drug and cytotoxicity assays performed on human fetal osteoblastic cells. The preliminary biological tests showed the lack of cytotoxicity of the hybrid material and suggest its potential role in bone tissue engineering applications.